Contaminação ambiental por compostos organoestânicos - Godoi, Ana Flavia Locateli; Favoreto, Rodrigo [UNESP]; Santiago-Silva, Mary [UNESP] (Sociedade Brasileira de Química, 2003)
The occurrence and the effects of organotin compounds (OTs) have been studied since a long time, due to their widespread use and deleterious effects. Some OTs are used as pesticides in crops, or as biocides in antifouling paints, applied in the ship hulls to avoid attachment and growth of tube worms, mussels and barnacles. However, nontarget organisms may be exposed, resulting in the poisoning of biological system, originating mutations and sentencing species to extinction. In this work we reported a revision study on the history of OTs and the techniques developed for its assessment and control.
Environmental contamination for organotin compounds
Keywords: organotin compounds; environment; analytical techniques